Communication framework for directed transmission of informative semantic - Guangming SHI; Minxi YANG; Dahua GAO; Jingxuan CHAI (Tongxin xuebao)
As the traditional communication development model focusing on enhancing bandwidth and spectrum efficiency is getting bottlenecked, more and more research is shifting the goal of intelligent communication from the syntactic level to the semantic level to save bandwidth resources by sensing and transmitting semantics rather than the complete signal.For the receiver agent, it is enough to receive only the information part of the understandable semantics.If the informative parts from the semantics can be filtered for transmission, it will further reduce the bandwidth resources and the time and power consumption of semantic information processing at the sender-side.To this end, firstly, the process of semantic information processing and comprehension of an intelligent body was explored.Secondly, the semantics perceived by the receiver from the message were classified into redundant semantics, unintelligible semantics, and informative semantic.Then, a communication paradigm oriented to transmitting the informative part of the semantics, called informative communication, was proposed, and the communication paradigm was extended to include four layers: syntax, semantic, informative, and pragmatic.Finally, the feasibility and effectiveness of informative communication were verified through simulation.This provides new ideas and technical traction for the development of next-generation communication models.